PEDAGOGICAL TOOLS AS A MEANS OF ENVIRONMENTAL TRAINING OF TECHNICAL UNIVERSITIES’ STUDENTS - E. G. Skibitskiy; T. I. Krune (Вестник Кемеровского государственного университета, 2014)
The paper deals with the problem of environmental training of technical universities’ students from the position of competence-based approach and provides a method for triggering the mechanism for increasing the level of environmental training, through the implementation of the developed pedagogical tools in the educational process. Tools components are described.